context considerate in structure and form types (zikr and hazf) in the explications of Al-Alfiyya of Ibn Malik: "Ibn Hisham, Al-Ashmouni and Ibn Akil as models" - العمر مازن; مالك يحيا; حكمت بربهان (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The study tackles an important syntactic subject; context considerate in structure and form types (zikr and hazf) in the explications of Al-Alfiyya of Ibn Malik: "Ibn Hisham, Al-Ashmouni and Ibn Akil as models" . It starts with the definition of context and its relation with syntax. It also explains zikr and hazf, as discussed by some Arabic scholars. Then it explores some examples of zikr and hazf, two of the most important grammatical forms used in Ibn Malik’s poem to express meanings, as required by context. As Arab grammarians started to derive rules and define speakers’ intentions, they took context into consideration. This is evident in their many statements, including "al-mubtada’, al-khabar or a verb may be deleted for context reuirements". This indicates that context was given due consideration in grammatical forms. Key words: context – form – zikr – hazf – intention.